Glycogen synthase kinase-3 and p38 MAPK are required for opioid-induced microglia apoptosis - Xie, Nanchang (2010)
Opioids have been widely applied in clinics as one of the most potent pain relievers for centuries, but their abuse has deleterious physiological effects beyond addiction. We previously reported that opioids inhibit cell growth and trigger apoptosis in lymphocytes. However, the underlying mechanism by which microglia apoptosis in response to opioids is not yet known. In this study, we show that morphine induces microglia apoptosis and caspase-3 activation in an opioid-receptor dependent manner. Morphine decreased the levels of microglia phosphorylated Akt (p-Akt) and p-GSK-3β (glycogen synthase kinase 3 beta) in an opioid receptor dependent manner. More interestingly, GSK-3β inhibitor SB216763 significantly increases morphine-induced apoptosis in both BV-2 microglia and mouse primary microglial cells. Moreover, co-treatment of microglia with SB216763 and morphine led to a significant synergistic effect on the level of phospho-p38 mitogen-activated protein kinase (MAPK). In addition, inhibition of p38 MAPK by its specific inhibitor SB203580 significantly inhibited morphine-induced apoptosis and caspase-3 activation. Taken together, our data clearly demonstrates that morphine induced apoptosis in microglial cells, which is mediated via GSK-3β and p38 MAPK pathways.